Acoustic Performance of Live Music Café as Broadcasting Studio Concept at Shop Houses in Surabaya - Prilya Lutvitania Pradita; Wiratno Argo Asmoro; Ima Defiana (Institut Teknologi Sepuluh Nopember, 2015)
The development of the business sector, cafe with live music performance in particular, is increasing in urban areas. In general, live music performance in the cafe was followed by a process of event recording, which then be broadcasted for marketing purposes. From this sequence of activities, arise the need of acoustic quality to meet the standard of acoustic comfort for cafe buildings. The selection of research subjects started by sampling a wide variety of cafe buildings in Surabaya, including the type of building, the volume and the ratio of the facade material. Field measurement depends with sampling data and existing circumstances. This paper is a preliminary study that focus to show the field studies. So the final result of this paper is the method and the results of field studies were applied in research workflow